A general neutral profits tax - Devereux, M; Freeman, H (1991)
It is widely agreed that, in the absence of specific corrective aims, the corporate tax system should aim for neutrality. A fully neutral tax would not affect the scale of a company's activities, nor the allocation of investment spending between different assets, nor the method by which this investment is financed. Moreover these properties should also hold under changing economic circumstances, particularly rising prices; in a world where inflation is endemic, for example, it is unrealistic to design a system which only functions well when inflation is zero.